(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
The development of the maritime region of Swahili Coast is linked to fragmentation, different colonial powers and opening dynamic. For centuries Arab, Persian, Indian traders setteled mostly on islands; then this migrant spread along the entire Coast from the Somali Coast, the Lamu Archipelago, Mombasa, Zanzibar, Pemba, Kilwa and the Comoro Islands south to Mozambique. After the XIII century the Swahili culture was dominated by ArabsÂ who arrived from the Hadramauth region in South Yemen. The arrival of the Portuguese in 1498 changed everything. First of all they sacked Mombasa and Kilwa and by 1530 they controlled the entire Coast. In 1652 the Omani Arabs took Zanzibar and in 1696 they conquered Mombasa. The essay analyze other main problems in the Swahili Coast: the trade in slaves in East Africa in the XVIII and early XIX centuries; the Qadiriyya and Shadhiliyya Brotherhoods; the Mawlid, the translations of the Quran in East African languages; the Mihadhara Public Preaching, Islamic Associations, Zanzibar Sufi Orders, etc.